Molecular Fingerprint Comparison of Closely Related Rose Varieties based on UHPLC‐HRMS Analysis and Chemometrics. Issue 1 (January 2017) - Riffault‐Valois, Ludivine; Blanchot, Lucille; Colas, Cyril; Destandau, Emilie; Pasquier, Laure; André, Patrice; Elfakir, Claire
Abstract: Introduction: The "Jardin de Granville" modern rose variety not only combines the morphological properties of its two parental cultivars, but also possesses better agronomic characteristics (abundant blooms, strong growth and vitality, high resistance to common rose diseases). In addition, it shows remarkable biological properties such as a high ability to decrease inflammatory and oxidative stress on skin cells. That is why Parfums Christian Dior selected this rose variety to be an active ingredient in luxury cosmetics. Objectives: To identify the characteristic molecular signature of "Jardin de Granville" compared with its parents "Annapurna" and "John Clare", by the mean of a non‐targeted metabolomic comparison. Material and Methods: Wood, flower and leaf hydro‐alcoholic extracts were analysed by UHPLC‐ESI‐HRMS. The fingerprints were then submitted to unsupervised multivariate analyses involving principal component analysis (PCA) and hierarchical ascendant classification (HAC). Analysis of variance (ANOVA) was finally performed to highlight the significant differences in each group of organs. Results: The extracts were composed of phenolic compounds such as hydrolysable and condensed tannins and flavonol derivatives. Three groups of extracts were clustered as a function of the variety. The compounds overexpressed in "Jardin de Granville" variety were highlighted thanks to ANOVA test. Flower was the most discriminative organ with 15 overexpressed molecules. Auto MS/MS analyses led to their tentative identifications. Conclusion: The non‐targeted metabolomic approach revealed the importance of tannins to discriminate close rose varieties. The overexpressed hydrolysable tannins characteristic of "Jardin de Granville" can be responsible for the antioxidant and anti‐inflammatory properties of the rose cosmetic ingredients. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Woods, leaves and flowers of three rose varieties were analyzed by UHPLC‐HRMS. The fingerprints were compared using PCA, HAC and ANOVA to highlight 'Jardin de Granville' characteristic molecular signature. Flower was the most discriminative organ with 15 overexpressed molecules, identified in majority as hydrolysable tannins.